Understanding on Bay’ As-Salam in gold online transaction : a study among UiTM Puncak Alam students / Mohamad Hasib Mawardi Mazlan - Mazlan, Mohamad Hasib Mawardi (2019)
Sale of greetings is a contract of sale where payment is made first and products are obtained later. Several scholars agreed on this belief but opposed to the opinions of the scholars who hold the Shaykh faith, which made it possible to offer cash and deferment. To people to get something, selling is a daily activity, selling in Islam has in compliance with Islamic law, its own laws and conditions make it a legal transaction. The Internet's role in human life has made the process of buying and selling simpler. Therefore, many advertisements are linked to the investment in gold attract students in high school. We are more likely to be influenced and more likely to be fooled by the more extreme cases of fraud for those who are an alphabet and do not understand gold trading. While some rules have been given by Islam to obey. The key aims of this research are studying the extent of student understanding of online gold purchasing with bay's greetings and examining the relationship between student learning history understanding of online gold purchasing transactions. The approach used in this analysis is quantitative use of statistics concise. The findings show that the degree of comprehension of the students is closely related to the context of their research. Based on this study, further study to enhance the quality of Islamic students is strongly encouraged.